Kto, kogo i do czego chce przekonać w "Politei" Platona? (O dwóch zderzających się nowych interpretacjach) = Who wants to persuade whom and to what in Plato`s "Republic"? (about two colliding new interpretations) - Zygmuntowicz, Dorota (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article discusses James L. Kastely`s, "The Rhetoric of Plato?s Republic. Democracy and the Philosophical Problem of Persuasion" (2015), in the context of later reading of the "Republic" by Jacob Howland, "Glaucon`s Fate. History, Myth, and Character in Plato`s Republic" (2018). The comparative background is the process of the act of persuasion: according to Howland, ineffective against Glaucon, and according to Kastely, affective in the world as it is.
Keywords: Plato (filozof; 427 p.n.e.-347 p.n.e.); "Politeia"; retoryka; perswazja; demokracja; filozofia; "Republic"; rhetoric; persuasion; democracy; philosophy